2021
DOI: 10.3390/biomedicines9080907
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Ginsenoside Rb1-Loaded Mesoporous Calcium Silicate/Calcium Sulfate Scaffolds for Inflammation Inhibition and Bone Regeneration

Abstract: Bone defects are commonly found in the elderly and athletic population due to systemic diseases such as osteoporosis and trauma. Bone scaffolds have since been developed to enhance bone regeneration by acting as a biological extracellular scaffold for cells. The main advantage of a bone scaffold lies in its ability to provide various degrees of structural support and growth factors for cellular activities. Therefore, we designed a 3D porous scaffold that can not only provide sufficient mechanical properties bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…could be attributed to the presence of tricalcium silicate (C3S) and dicalcium silicate (C2S), respectively, emerged when CS particles were introduced to the PEGDA solution [24]. As expected, the intensities of the peaks corresponding to the calcium silicate were increased, while those corresponding to the PEGDA were decreased, when the CS content in PEGDA was increased from 10 wt% (CS10) to 20 wt% (CS30) [25].…”
Section: Synthesis and Characterization Of The Light-curable Cs Compositesupporting
confidence: 58%
See 1 more Smart Citation
“…could be attributed to the presence of tricalcium silicate (C3S) and dicalcium silicate (C2S), respectively, emerged when CS particles were introduced to the PEGDA solution [24]. As expected, the intensities of the peaks corresponding to the calcium silicate were increased, while those corresponding to the PEGDA were decreased, when the CS content in PEGDA was increased from 10 wt% (CS10) to 20 wt% (CS30) [25].…”
Section: Synthesis and Characterization Of The Light-curable Cs Compositesupporting
confidence: 58%
“…A strong and broad peak in the 2θ range between 20° and 25° can be seen in the XRD pattern of CS0, indicating the amorphous nature of PEGDA specimens. In contrast, newly formed characteristic peaks located at 29.6° and 32.6°/34.2°, which could be attributed to the presence of tricalcium silicate (C3S) and dicalcium silicate (C2S), respectively, emerged when CS particles were introduced to the PEGDA solution [ 24 ]. As expected, the intensities of the peaks corresponding to the calcium silicate were increased, while those corresponding to the PEGDA were decreased, when the CS content in PEGDA was increased from 10 wt% (CS10) to 20 wt% (CS30) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Si ions have been demonstrated to promote vascularization by inducing secretion of angiogenic-related factors from nearby fibroblasts [ 23 ]. Furthermore, the release of Si ions were also proven to regulate bone or tooth regeneration in various types of stem cells, notably hDPSCs [ 24 , 25 ]. Dashnyam et al concluded that the release of appropriate Si ions, up to several ppm, into the surrounding fluid had several roles to play in increasing angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous calcium-silicate nanoparticles (MCSNs) have been reported as an ideal carrier for various bioactive molecules delivery due to their special porous structures and excellent biocompatibility [ 12 , 13 , 14 , 15 , 16 ]. MCSNs have been widely used to deliver antibiotics, anti-cancer drugs, and other chemicals [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%